2017
DOI: 10.18103/mra.v5i6.1297
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hysterosalpingography and laparoscopy in evaluation of female infertility

Abstract: Background and Objectives: Laparoscopic surgery (LS) is the most important diagnostic technique for the detection of causes of infertility; however, this method is accompanied by some setbacks. Given the noninvasive nature and cost-effectiveness of hysterosalpingography (HSG), it is widely used as the first-line approach for the evaluation of the patency of the fallopian tubes and uterine anomalies in female infertility. Herein, we aimed to compare the diagnostic values of HSG with LS in the assessment of pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…We found 93% accuracy of HSG in tubal pathology diagnosis, similar results were reported by previous studies [16,17]. Lavy, et al [18] concluded that in 95% of patients with normal HSG or suspicious unilateral obstructed tube, laparoscopy is not indicated, and patient management will not be altered.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…We found 93% accuracy of HSG in tubal pathology diagnosis, similar results were reported by previous studies [16,17]. Lavy, et al [18] concluded that in 95% of patients with normal HSG or suspicious unilateral obstructed tube, laparoscopy is not indicated, and patient management will not be altered.…”
Section: Methodssupporting
confidence: 89%
“…In agreement with the previous study [16], we found that the accuracy of HSG in the diagnosis of peri tubal adhesions was 84%.…”
Section: Main Pointssupporting
confidence: 93%
“…The HSG remains the first-line examination in the exploration of tubal infertility [7][8][9]. Its positive predictive value was 58.1%, superimposable to that reported by Bosteels [10].…”
Section: Discussionmentioning
confidence: 61%
“…Infertility is a disease of couples due to failure to achieve clinical pregnancy even after 12 months of regular unprotected intercourse. 1 It may be primary or secondary. In primary infertility clinical pregnancy was never documented and secondary infertility refer to a couple where there was documented clinical pregnancy but failed to conceive subsequently.…”
Section: Introductionmentioning
confidence: 99%